Mediating Controversial Technology: The Case of Monsanto's Attempt to Introduce Genetically Modified Wheat in North Dakota - Sullivan, Dale (HERMES - Journal of Language and Communication in Business, 2006)
When Monsanto attempted to release transgenic wheat in the upper Midwest of the U.S., localization efforts to accommodate stakeholders were unsuccessful. This paper explores this break down, focusing on the rhetoric of a group of people who attempted to establish protocols that would make co-existence between transgenic and organic producers possible. Their goal was to document best management practices that would satisfy both parties. The case points to the need for co-existence groups of this kind, but also indicates that there is still much we need to learn about negotiating controversial technology.